Strategi Pembelajaran Bahasa Indonesia bagi Penutur Asing dengan Buku Saku Vokal Sederhana: Kajian Literatur (International Forum of Researchers and Lecturers, 2024)
Learning Indonesian for foreign speakers faces various challenges, especially in mastering vowels which are an important component in communication. This article aims to examine effective Indonesian language learning strategies using simple vowel pocket books through a literature review. This study involves an analysis of theories and approaches in second language learning, as well as the importance of vowel mastery. The methodology used is a literature review by examining various relevant sources and case studies. The results of the study indicate that simple vowel pocket books are effective in improving the pronunciation and understanding of Indonesian vowels for foreign speakers. This pocket book has also been shown to increase student motivation and involvement in the learning process. The implications of this study emphasize the importance of integrating practical and user-friendly learning aids to support the success of Indonesian language learning.